Integrating Artificial Intelligence (AI) in Language Teaching: Effectiveness, Challenges, and Strategies - Mananay, Janet Alesna (International Journal of Learning, Teaching and Educational Research, 2024)
Integrating artificial intelligence (AI) technologies into various domains of education has emerged as a promising avenue for enhancing teaching and learning experiences. Language teaching, in particular, benefits significantly from AI’s capabilities, offering unprecedented opportunities to support educators in delivering more effective and personalized instruction to diverse student populations. The research employed a mixed-method approach using a quant-qual research design. to investigate AI’s integration into language teaching. Results from n=100 language teachers indicate that educators perceive AI to be effective across multiple aspects. Different AI systems have varying levels of perceived effectiveness but are nevertheless welcomed positively. From the profile of teachers using AI, to the kinds of AI used and functions, there are varying distinctions as well as the acceptance of AI integration in language instruction. The fact that AI is being widely used to improve language instruction through interactive simulations, adaptive learning, and individualized feedback is evidence of this. Despite challenges such as technological constraints and pedagogical alignment, educators have reported successes in improving student engagement, proficiency, and autonomy through the strategic use of AI. These insights underscore the importance of continued exploration and implementation of innovative strategies to harness the full potential of AI in language education.